Respiratory Tract Infections in Inflammatory Bowel Disease Patients Taking Vedolizumab: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Marafini, Irene; Troncone, Edoardo; Rocchetti, Irene; Monteleone, Giovanni (Frontiers in Pharmacology, 2021)
The ongoing COVID-19 pandemic has raised concerns about the risk of SARS-CoV-2 infection in patients with Crohn’s disease (CD) and patients with ulcerative colitis (UC) taking immunosuppressants or biologics. We conducted a systematic review and meta-analysis to assess the risk of respiratory infections in patients with inflammatory bowel disease (IBD) treated with vedolizumab. We searched PubMed, EMBASE and Scopus to identify randomized controlled trials (RCT) comparing vedolizumab to placebo in patients with IBD. Outcomes were the rate of respiratory tract infections (RTI), upper respiratory tract infections (URTI) and lower respiratory tract infections (LRTI) among patients receiving vedolizumab as compared with placebo. Pooled rates were reported as Odds Ratios (OR) with 95 % Confidence Interval (CI). Eight RCT involving 3287 patients (1873 CD and 1415 UC) were analysed; 2493 patients received vedolizumab and 794 received placebo. The rates of RTI and URTI were statistically higher in vedolizumab-treated patients compared to placebo [OR= 1.63; 95% CI (1.07-2.49); OR=1.64 95% CI (1.07-2.53) respectively]. UC patients, but not CD patients, receiving vedolizumab had a higher risk to develop RTI and URTI [OR =1.98; 95% CI (1.41-2.77); OR =2.02; 95% CI (1.42-2.87)] compared to placebo-treated patients. The number of LRTI was small in both treatment groups. Data confirm the good safety profile of vedolizumab even though RTI were more frequent in patients receiving vedolizumab and the risk of URTIs was significantly higher in patients with UC.